The Influence of Airline Image and Service Quality on Purchase Intention and Its Impact on Passenger Loyalty of Lion Air - Gunawan, Guntur; Indrinanto, Agoes Tinus Lis; Padmalia, Metta (Journal Research of Social Science, Economics, and Management, 2025)
Lion Air is the airline remaining in operation in Indonesia, serving the community’s air transportation requirements. This airline charges low fares. The level of service quality impacts customer loyalty, particularly in transport services. In this context, the three categories of service quality are pre-, in-, and post-flight. This study adopts SERVQUAL Theory and Loyalty Theory as a theoretical review. This research used a quantitative methodology. SEM PLS via route analysis will be used to analyze the gathered data. A total of 260 samples were utilized. According to the study’s findings, purchasing intention is positively and significantly impacted by airline image and service quality. Customer loyalty is positively and significantly impacted by purchase intention. Service quality and airline image have a major indirect impact on loyalty via purchasing intention. Thus, purchase intention is a mediating variable that connects customer perceptions of image and service with their decision to remain loyal to Lion Air. This finding provides important implications for Lion Air management to focus on building a positive image and consistency in service to encourage purchase intention and increase customer loyalty in the long term.